Edukasi Keluarga tentang Peran Kehadiran Seorang Pendamping dalam Persalinan - Sari, Rury Narulita Sari; Sundari; Elita Chobi Baitu Uma (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2024)
Childbirth is a very meaningful event for a woman. Childbirth can be a positive and stressful experience for the mother and family. Waiting for the arrival of a new member in the family is eagerly awaited not only by mothers but also by husbands and families. While waiting for the first stage of labor, the mother needs support, one of which is the presence of someone who is considered important by the mother, such as her husband or family. The purpose of this service is to provide education to families about the role of a companion in childbirth. This community service was carried out at PMB Atika, Dolopo, Madiun Regency on December 3 2024. This community service is carried out by providing education to families or companions of mothers giving birth about the active role of a companion's presence in supporting and carrying out activities that can provide comfort for the mother. This community service activity went well and smoothly, it can be seen from the participants paying attention to the explanation about the active role of birth attendants which includes verbal support, physical contact, and choosing positions that are allowed to reduce pain in mothers giving birth, supported by enthusiasm for asking questions. The conclusion obtained is that the active role of the presence of a birth companion can have a positive influence on the mother during the first stage of labor.